Control interno administrativo y su incidencia en los procesos contables de la empresa Plantsforest S.A cantón Quevedo año 2023. - Rivera Rivera, Dayana Yaritza (2025)
The research evaluated the impact of administrative internal control on the accounting processes of Plantsforest S.A., located in the Quevedo canton, during the year 2023, identifying deficiencies related to non-compliance with the internal manual, which affected the accuracy of administrative management and the efficiency of accounting procedures. Weaknesses in the internal management and operations of the accounting area were exposed, which could have impacted the financial and operational performance of the company. The general objective was to evaluate the impact of internal control on accounting processes, identifying critical areas for its intervention, and the specific objectives included the analysis of internal regulations, the components of internal control and the level of training of administrative personnel. The methodology used was a mixed approach, combining qualitative and quantitative methods, using techniques such as direct observation, interviews and questionnaires. The results made it possible to identify weaknesses in internal control, which led to the proposal of improvement actions aimed at strengthening compliance with the manual, optimizing decision-making, increasing transparency and reducing operational and financial risks.